The Effects of Mycorrhiza Application on Vegetative and Generative Growth in Pepper (Capsicum annuum L.) Plants under Water Deficiency Conditions - Kamile Ulukapı; Zehra Kurt; Sevinc Sener (Turkish Journal of Agriculture: Food Science and Technology)
Arbuscular mycorrhizal fungi (AMF), which are beneficial soil organisms, have an important role in the uptake of plant nutrients by roots and thus help to healthy plant growth. The aim of this study was to determine the effects of AMF inoculation on the development of water-deficiency applied pepper plants. In this study, Tesla F1 pepper cultivars, Glomus etunicatum inoculated and without Glomus etunicatum, were exposed to four different irrigation regimes (25I, 50I, 75I, 100I). At the end of the experiment these plants were compared in terms of some vegetative and fruit properties. For this purpose, at the end of the trial; shoot length (cm), root length (cm), root spread (cm), number of leaves, leaf width and length (mm), stem diameter (mm), fruit width (mm), fruit length (mm), root and shoot weights (g), fruit pH, total soluble solid content and chlorophyll index were measured. P (phosphorus) and K (potassium) contents of leaves samples taken from plants were determined. As a result, it was determined that 75I irrigation regime gave the best results in terms of both plant growth and fruit properties in all mycorrhizal and non-mycorrhizal plants. It was also concluded that 75% irrigation level is sufficient for plant growth.